ANALISIS MANAJEMEN RANTAI PASOK (SUPPLY CHAIN MANAGEMENT) SUSU SAPI PERAH PADA KOPERASI PETERNAK GALUR MURNI DI KECAMATAN SUMBERBARU KABUPATEN JEMBER - Mahlidatul Isnia; Yuli Hariyati; Ati Kusmiati (University of Jember, 2017)
Koperasi Peternak Galur Murni is a business in the field dairy farm that located in the Sumberbaru District, Jember Regency. This research aimed to determine: (1) identify the product flow, the financial flow and the information flow in supply chain of dairy cattle, (2) the performance in supply chain of dairy cattle, (3) the value added processing of dairy cattle. The research was deliberately condusted in Sumberbaru district Jember regency. The descriptive and analytical methods are applied in this research. Data analysis tools used are Supply Chain Operation Reference method and value added analysis with Hayami method. The result analysis showed that: (1) there are three flows in supply chain of dairy cattle in Jember Regency, that are the product flow, the financial flow and the information flow that is not optimal, (2) Measuring the performance in supply chain of dairy cattle in the Koperasi Peternak Galur Murni on the Reliability attribute and Responsiveness showed good performance. Then, the Agility attribute, Costs, and Assets show performance is not good. (3) Koperasi Peternak Galur Murni was able to provide a positive added value in the form of processed pasteur milk and yoghurt with the average added value of Rp 5.194,39 per liter with ratio 28,86% and processed yoghurt of Rp. 7.987,78 with ratio 36,31%.